Damage evolution in reinforced concrete columns subjected to biaxial loading - Hugo Rodrigues (2013)
An analysis of the damage observed in 24 reinforced concrete (RC) columns tested under uniaxial and biaxial horizontal loading is presented. The test results show that for biaxial loading conditions specific damage occurs for lower drift demands when compared with the corresponding uniaxial demand (a reduction of 50-75 % was found). The damage distribution observed in each column is also analysed. No significant differences are found in the plastic hinge length for uniaxial and biaxial loading. The drift demands associated with each damage state are compared with reference values proposed in international guidelines. Finally, and based on the philosophy of the Park and Ang uniaxial damage index, two new expressions are proposed for the evaluation of damage in RC elements under biaxial loading. The results of the application of these expressions to the experimental results are discussed.